A high-throughput screening RT-qPCR assay for quantifying surrogate markers of immunity from PBMCs - Browne, Daniel J.; Kelly, Ashton M.; Brady, Jamie L.; Doolan, Denise L. (Frontiers in Immunology, 2022)
Immunoassays that quantitate cytokines and other surrogate markers of immunity from peripheral blood mononuclear cells (PBMCs), such as flow cytometry or Enzyme-Linked Immunosorbent Spot (ELIspot), allow highly sensitive measurements of immune effector function. However, those assays consume relatively high numbers of cells and expensive reagents, precluding comprehensive analyses and high-throughput screening (HTS). To address this issue, we developed a sensitive and specific reverse transcription-quantitative PCR (RT-qPCR)-based HTS assay, specifically designed to quantify surrogate markers of immunity from very low numbers of PBMCs. We systematically evaluated the volumes and concentrations of critical reagents within the RT-qPCR protocol, miniaturizing the assay and ultimately reducing the cost by almost 90% compared to current standard practice. We assessed the suitability of this cost-optimized RT-qPCR protocol as an HTS tool and determined the assay exceeds HTS uniformity and signal variance testing standards. Furthermore, we demonstrate this technique can effectively delineate a hierarchy of responses from as little as 50,000 PBMCs stimulated with CD4+ or CD8+ T cell peptide epitopes. Finally, we establish that this HTS-optimized protocol has single-cell analytical sensitivity and a diagnostic sensitivity equivalent to detecting 1:10,000 responding cells (i.e., 100 Spot Forming Cells/106 PBMCs by ELIspot) with 95% confidence. We anticipate this assay will have widespread applicability in preclinical and clinical studies, especially when samples are limited, and cost is an important consideration.